Overexpression of PPT2 Represses the Clear Cell Renal Cell Carcinoma Progression by Reducing Epithelial-to-mesenchymal Transition - Yuan, ChangFei (J Cancer, 2020)
Clear cell renal cell carcinoma (ccRCC) is one of the most common malignant tumors of the urinary system and has a poor response to radiotherapy and chemotherapy. To date, it is urgent to find effective biomarkers for the prevention and treatment of ccRCC. The occurrence and development of ccRCC is closely related to metabolic disturbances. Palmitoyl protein thioesterase 2 (PPT2) is a lysosomal thioesterase which is highly associated with metabolism, and it has never been studied in ccRCC. In this study, we first revealed PPT2 is significantly downregulated in ccRCC, and its expression level is highly correlated with clinicopathological parameters of ccRCC patients. Our ROC curve analyses evaluated the potential of PPT2 as a novel diagnostic marker and prognostic factor. Functional experiment results showed overexpression of PPT2 represses the proliferation, migration and invasion of ccRCC cells in vitro. Mechanistic investigations demonstrated that overexpression of PPT2 represses the ccRCC progression by reducing epithelial-to-mesenchymal transition (EMT). In conclusion, PPT2 is downregulated in ccRCC. Decreased PPT2 expression may be considered as a novel diagnostic marker and prognostic factor and serve as a therapeutic target for ccRCC.